Istota i znaczenie rachunku technicznego dla oceny rentowności zakładów ubezpieczeń - Spigarska, Ewa (Essence and Significance of Technical Account for Insurance Companies Profitability Assessment, 2006)
One of the most important segments of the financial market is an insurance activity. The main goal for the insurance company is a risk assurance, and this is the insurance subject; however as economic entity they aim at profitability. Technical result of insurance company depends on a risk level, what is reflected in the insurance premium level, deposits security and harmfulness thus in the claim cost levels, technical reserves size and reassurance cession size.One of the most important segments of the financial market is an insurance activity. The main goal for the insurance company is a risk assurance, and this is the insurance subject; however as economic entity they aim at profitability. Technical result of insurance company depends on a risk level, what is reflected in the insurance premium level, deposits security and harmfulness thus in the claim cost levels, technical reserves size and reassurance cession size.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 545-554